NEDD8 promotes radioresistance via triggering autophagy formation and serves as a novel prognostic marker in oral squamous cell carcinoma - Yuan, Tsu-Zong; Lin, Hui-Yu; Kuei, Chia-Hao; Lin, Che-Hsuan; Lee, Hsun-Hua; Lee, Hsin-Lun; Lu, Hsiao-Wei; Su, Chia-Yi; Chiu, Hui-Wen; Lin, Yuan-Feng (Cancer cell international, 2023)
Radiotherapy is the first-line regimen for treating oral squamous cell carcinoma (OSCC) in current clinics. However, the development of therapeutic resistance impacts the anticancer efficacy of irradiation in a subpopulation of OSCC patients. As a result, discovering a valuable biomarker to predict radiotherapeutic effectiveness and uncovering the molecular mechanism for radioresistance are clinical issues in OSCC. Three OSCC cohorts from The Cancer Genome Atlas (TCGA), GSE42743 dataset and Taipei Medical University Biobank were enrolled to examine the transcriptional levels and prognostic significance of neuronal precursor cell-expressed developmentally downregulated protein 8 (NEDD8). Gene set enrichment analysis (GSEA) was utilized to predict the critical pathways underlying radioresistance in OSCC. The colony-forming assay was used to estimate the consequences of irradiation sensitivity after the inhibition or activation of the NEDD8-autophagy axis in OSCC cells. NEDD8 upregulation was extensively found in primary tumors compared to normal adjacent tissues and potentially served as a predictive marker for the therapeutic effectiveness of irradiation in OSCC patients. NEDD8 knockdown enhanced radiosensitivity but NEDD8 overexpression reduced it in OSCC cell lines. The inclusion of MLN4924, a pharmaceutical inhibitor for NEDD8-activating enzyme, dose-dependently restored the cellular sensitivity to irradiation treatment in irradiation-insensitive OSCC cells. Computational simulation by GSEA software and cell-based analyses revealed that NEDD8 upregulation suppresses Akt/mTOR activity to initiate autophagy formation and ultimately confers radioresistance to OSCC cells. These findings not only identify NEDD8 as a valuable biomarker to predict the efficacy of irradiation but also offer a novel strategy to overcome radioresistance via targeting NEDD8-mediated protein neddylation in OSCC.